2019
DOI: 10.3390/s19153357
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Carbon Dioxide Using Hollow-Core Photonic Crystal Fiber Mach–Zehnder Interferometer

Abstract: Monitoring of greenhouse gases is essential to understand the present state and predict the future behavior of greenhouse gas emissions. Carbon dioxide (CO2) is the greenhouse gas of most immediate concern, because of its high atmospheric concentration and long lifetime. A fiber-optic Mach–Zehnder interferometer (MZI) is proposed and demonstrated for the laboratory-scale monitoring of carbon dioxide concentration. The interferometric sensor was constructed using a small stub of hollow-core photonic crystal fib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 32 publications
0
11
0
Order By: Relevance
“…With remarkably quick reaction and recovery times, the sensor demonstrated consistent and accurate detection of CO2 concentrations. The schematic presented in Figure 3 (b) is used to characterize CO2 gas concentration in near atmospheric pressure [58]. The fiber-optic technology has promise for monitoring CO2 content and leakage in the environment, according to the experimental research of this work [58].…”
Section: Toxic Gas Monitoring Sensorsmentioning
confidence: 99%
See 2 more Smart Citations
“…With remarkably quick reaction and recovery times, the sensor demonstrated consistent and accurate detection of CO2 concentrations. The schematic presented in Figure 3 (b) is used to characterize CO2 gas concentration in near atmospheric pressure [58]. The fiber-optic technology has promise for monitoring CO2 content and leakage in the environment, according to the experimental research of this work [58].…”
Section: Toxic Gas Monitoring Sensorsmentioning
confidence: 99%
“…For environmental monitoring applications, a hollow core Photonic crystal fiber (HC-PCF)-based MZI is presented that can detect ambient CO2 levels as shown in Figure 3 (a) [58]. A stub of HC-PCF was sandwiched between a lead-in and lead-out SMF to create the device.…”
Section: Toxic Gas Monitoring Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Many of the sensors proposed to date either have complex configurations or poor sensitivity and response time for high-resolution measurement of gases. Ahmed et al [39] reported a highly sensitive MZI structure that uses a small stub of HC-PCF for monitoring of CO 2 ; however, a detailed study on such a configuration is necessary to better understand its performances and to explore other potential applications. Recently, we studied length-dependent performance of these devices to understand their sensing properties [40].…”
Section: Introductionmentioning
confidence: 99%
“…Since precious metals such as gold and platinum are often used as sensitive materials in Plasmonic sensors, the cost of manufacturing these types of sensors is high. Recently, the Hollow-core photonic crystal fibers (HC-PCFs) based Mach-Zehnder interferometer MZI method has been investigated for the detection and measurement of CO2 [17]. There are three types of piezoelectric gas sensors: surface sound wave (SAW), quartz crystal microbalance (QCM) [18], and microelectromechanical systems (MEMS) [19,20].…”
mentioning
confidence: 99%